If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 = x + z Solving -10 = x + z Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -10 + -1x = x + -1x + z Combine like terms: x + -1x = 0 -10 + -1x = 0 + z -10 + -1x = z Add '10' to each side of the equation. -10 + 10 + -1x = 10 + z Combine like terms: -10 + 10 = 0 0 + -1x = 10 + z -1x = 10 + z Divide each side by '-1'. x = -10 + -1z Simplifying x = -10 + -1z
| -3x-15=-3(x+5) | | 5+6[x+1]=11+5x | | 9y-4*y+5=40 | | X-16y=8 | | 3.6666(12-a)=43 | | x+16/-6=-6 | | 0.1x=6.61 | | -2*w-7+10w=34 | | 7x+20=2x+20 | | 10x-9=41+8x | | x+10/22+87/x | | 20=8+3*12+4x | | 5y+11=8y-4 | | 3x+16/2=5 | | 2r-1.6=-5.6 | | 6*n=x | | 6*n-5-11n=0 | | -4y-8=-4 | | 2x-7+x=8 | | 7+4*2a+15=-13 | | 159=-2x+3 | | 8y+3(y-2)=4(y+1)-2 | | 4x-(x-15)=6(10-x)+4x | | 0,5y-14=34,5/13 | | -5/7y=30 | | -2(5t-4)+7t=2t-3 | | -3w/5=18 | | 4(x-4)=8(x+1) | | h-9=-19 | | -15=-5/9v | | 9y-2+4=31 | | 2(x-4)+3x=3x-2 |